Comparison for Chinese subordinates as a motivation approach: Scale development and psychometric properties - Jingjing Ge; Yezhuang Tian; Chengfeng Li (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Chinese people are motivated by social comparison and temporal comparison. Based on this finding, we conceptualized lateral comparison and vertical comparison as two distinct constructs that represent individual self-enhancement toward the nature of social comparison with others and temporal comparison with self over time. We hypothesized that as stable individual psychological difference, lateral comparison and vertical comparison would have differential effects on people's working behavior in the Chinese organizational context. Design/methodology/approach: Based on a conceptualization approach to Chinese management research, we conducted three studies to develop and validate a two-factor comparison scale which includes three-item lateral comparison and a three-item vertical comparison. Findings: Results from qualitative data in Study 1 provide evidence of convergent and discriminate validity of the scale, while Study 2 demonstrates the scale's predictive validity. Furthermore, in Study two, a field survey in multiple Chinese organizations showed that lateral comparison and vertical comparison had differential effects on employee task performance and organizational citizenship behavior. Research implications: The theoretical and practical implications of this study are discussed in the working context in Chinese organizations and beyond. Originality/value: This finding integrates insights from previous research in social comparison and temporal comparison into a motivation approach that supervisors use toward subordinates in the Chinese organizational context.
Keywords: 650; lateral comparison; vertical comparison; task performance; organizational citizenship behavior; scale development